Profiling Model Digitalisasi Administrasi Pajak di Kota Malang: Sanksi, Pemeriksaan, Sosialisasi dan Pelayanan Perpajakan - Puspita, Ayu Fury; Pusposari, Devi (International Journal of Social Science and Business, 2024)
Despite various strategies implemented by the Malang City Government to optimize local tax revenue, taxpayer compliance has not improved as anticipated. This study aims to analyze the impact of sanctions, inspections, socialization, and tax services on taxpayer compliance, contributing to the development of a digital tax administration model in Malang City. Utilizing a quantitative approach, data were collected through online questionnaires from 210 taxpayers and analyzed using multiple regression with SPSS software. The results revealed that sanctions, inspections, socialization, and tax services significantly influence taxpayer compliance. These findings suggest that a balanced approach incorporating both strict enforcement measures such as sanctions and inspections, alongside proactive engagement through socialization and improved tax services, can enhance compliance. This integrated strategy is essential for the digitalization of tax administration in Malang, aiming to make the system more efficient and user-friendly, thereby potentially increasing taxpayer compliance.